2017
DOI: 10.1038/cdd.2017.94
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and IAPs co-operate to protect tumors from cytotoxic lymphocyte-derived TNF

Abstract: Smac-mimetics are emerging as promising anti-cancer agents and are being evaluated in clinical trials for a variety of malignancies. Smac-mimetics can induce TNF production from a subset of tumor cells and simultaneously sensitize them to TNF-induced apoptosis. However, TNF derived from other cellular sources, such as cytotoxic lymphocytes (CLs) within the tumor, may also contribute to the anti-tumor activity of SMs. Here, we show that CD8 T cells and NK cells potently kill tumor cells in the presence of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…The fact that TNFR2 was identified here in a pooled screen setting points to a cell-intrinsic function of TNFR2 in enhancing cell death. Intriguingly, a recent study found the birinapant to enhance cell killing via the membrane bound form of TNFα (60). In light of our findings, it will thus be interesting to evaluate a possible role for TNFR2 in these settings and whether sensitivity to SMAC mimetic treatment is correlated with TNFR2 expression.…”
Section: Discussionmentioning
confidence: 58%
“…The fact that TNFR2 was identified here in a pooled screen setting points to a cell-intrinsic function of TNFR2 in enhancing cell death. Intriguingly, a recent study found the birinapant to enhance cell killing via the membrane bound form of TNFα (60). In light of our findings, it will thus be interesting to evaluate a possible role for TNFR2 in these settings and whether sensitivity to SMAC mimetic treatment is correlated with TNFR2 expression.…”
Section: Discussionmentioning
confidence: 58%
“…Together, these results suggested that the combination of the Immune Checkpoint Inhibitor (ICI), anti-PD1, and birinapant would be a very effective way to increase CL killing. And indeed, this is what the authors observed [149]. Similarly, Beug and colleagues in an extensive and very detailed study, showed that combining the ICIs, anti-PD1 or anti-Cytotoxic T-Lymphocyte-Associated protein 4 (anti-CTLA-4), with the SM LCL161 greatly increased survival in intra-cranial mouse glioblastoma models and produced durable cures [150].…”
Section: Combination With Immunotherapymentioning
confidence: 64%
“…Upon antigen recognition or NK-activating receptor activation, CLs naturally respond by inducing TNF. Surprisingly, given the data showing the ability of SMs to increase TNF levels, birinapant did not increase T-cell production of TNF [149]. On the other hand, tumor-derived Programmed Death-Ligand 1 (PD-L1) engagement of its receptor, Programmed cell Death protein 1 (PD-1), expressed on CLs, decreased CL production of TNF.…”
Section: Combination With Immunotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…PD-L1 expression on CD11b þ MDSCs also impedes the early adaptive immune response to SMAC mimetic monotherapy (16). Several groups have shown that the induction of effective adaptive antitumor immunity with either radiation or a SMAC mimetic compound requires blockade of the PD-1/PD-L1 immune checkpoint (16,20,49), and Deng and colleagues showed that this was dependent upon TNFa-mediated clearance of CD11b þ Gr-1 þ cells (4). It is certainly plausible that additional therapeutic synergy could be achieved by triple therapy: ART, Debio 1143, and PD-1/PD-L1 inhibition.…”
Section: Discussionmentioning
confidence: 99%